The dragon in the volcano - Klimo, Kate; Shroades, John (New York : Random House, 2011)
Emmy the dragon is maturing and growing too large--and bored--for her quarters, but when she disappears her Keepers, cousins Jesse and Daisy, follow her trail to the Fiery Realm in hopes of bringing her home
008-012
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Lost articles -- Juvenile fiction; Volcanoes -- Juvenile fiction; Cousins -- Juvenile fiction; Dragons -- Fiction; Magic -- Fiction; Lost and found possessions -- Fiction; Volcanoes -- Fiction; Cousins -- Fiction; Fiction